Odpowiedzi

2009-12-02T21:04:52+01:00
Y + 2 - (3 - x) = 0
x - 2 = 5 - (2 - y)

y+2-(3-x)=0
y+2-3+x=0
y-1+x=0
y=1-x

x-2=5-2+1-x
2x=6
x=3

y=1-x
y=1-3
y=-2

x=3
y=-2

To jest poprawne rozwiązanie

1 5 1
Najlepsza Odpowiedź!
2009-12-02T21:06:44+01:00
Y + 2 - (3 - x) = 0
x - 2 = 5 - (2 - y)

y +2-3+x=0
x-2=5-2+y

y=0-2+3-x
x-2=5-2+0-2+3-x

y=0-2+3-x
x+x= 5-2+0-2+3+2

y=0-2+3-x
2x= 6 / ÷ 2

y=0-2+3-x
x=3

x=3
y=0-2+3-3

x=3
y=-4
1 5 1
2009-12-02T21:09:22+01:00
Y + 2 - (3 - x) = 0
x - 2 = 5 - (2 - y)

y+2-3+x=0
x-2=5-2+y
x=3+y+2
x=5y

y+2-3+5y=0
6y=1/:6
y=¹/₆

x=5y
x= 5x¹/₆
x=⁵/₆